Talent Management in Healthcare: The New Strategic Objective - Marçal Gomes, Silvia (Journal of Organizational Psychology, 2024)
In today’s rapidly evolving healthcare landscape, effective talent management has become a critical priority for any organization seeking exceptional and safe care, whilst driving a positive outcome and impact in people’s lives. This article delves into the intricacies of talent management in healthcare, from an operational standpoint, aiming to capture how the frontline workforce perceives talent management. It is hypothesized that by implementing comprehensive talent management strategies, healthcare institutions would be able to address the current challenges posed by the worldwide workforce shortages. The increasing demand for healthcare services has prompted organizations and governments to proactively approach talent management to attract and retain the right individuals with the right skills to remain competitive and even functional. Employee engagement initiatives, along with a robust culture of continuous learning and phycological safety, where individuals can be at optimal performance and positively impact patient experience and outcome, significantly reduce turnover rates and ensure workforce stability (Dyrbye et al., 2017).